(untitled) (Balthazar, 2022)
The following article proposes to reframe and develop the concept of «speciesism» as a sacrificial norm. The hinge around which this norm is developed is that of «species» whose political/performative connotation is obscured by the supposed objectivity of a scientific lexicon. Therefore, the following pages propose a deconstruction of such a concept and suggest an alternative way to oppose the speciesist machine: the anti-speciesism of the common.